Gazelles as Job Creators: A Survey and Interpretation of the Evidence - Magnus Henrekson; Dan Johansson (Research Institute of Industrial Economics (IFN), 2008)
It is often claimed that small and young firms account for a disproportionately large share of net employment growth. We conduct a meta analysis of the empirical evidence regarding whether net employment growth rather is generated by a few rapidly growing firms so-called Gazelles that are not necessarily small and young. Gazelles are found to be outstanding job creators. They create all or a large share of new net jobs. On average, Gazelles are younger and smaller than other firms, but it is young age more than small size that is associated with rapid growth. Gazelles also seem to be overrepresented in services.
Keywords: D21; L25; M13; O10; O40; 330; Entrepreneurship; Firm Growth; Flyers; Gazelles; High-growth Firms; Job Creation; Rapidly Growing Firms; KMU; Unternehmenswachstum; Personalplanung; Beschäftigungseffekt; Großbritannien; Schweden; USA